Down by the riverside - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Historically, Egypt, and to a lesser extent Sudan, virtually monopolised the use of the waters of the river Nile, for water supply, irrigation and electricity. This was at the expense of the other riparian (riverside) states, but nowadays the trend...